Efficacy of rituximab in patients with rheumatoid arthritis - Muhammad Bilal; Ullah , Ansar; Khattak, Saima (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the efficacy of rituximab 2×500mg in rheumatoid arthritis patients. Methods: The descriptive case series was conducted at the Department of General Medicine, Lady Reading Hospital, Peshawar, Pakistan, from November 25, 2018, to May 24, 2019, and comprised patients of either gender aged 30-60 years with rheumatoid arthritis diagnosis for >6 months. The patients received 2 doses of rituximab 2×500mg through intravenous infusion with pre-medications as a standard protocol. A follow-up visit was recommended for each patient after 24 weeks. The efficacy of the treatment in terms of disease progression and improvement were observed using the Disease Activity Score-28 scale at the baseline and on follow-up. Data was analysed using SPSS 20. Results: Of the 97 patients, 83(85.6%) were female and 14(14.4%) were male patients. The overall mean age was 50.68±14.27 years. The baseline score was 6.68±1.14 while the follow-up score was 4.62±0.93 (p<0.05). In terms of efficacy, 25(25.8%) patients showed no improvement, while 72(74.2%) had improvement. Conclusions: Rituximab 2×500mgI was found to be an effective treatment option for rheumatoid arthritis patients. Key Words: Rituximab, Disease-modifying antirheumatic drug, DMARD, Rheumatoid arthritis, Efficacy, DAS-28 score.